Cassava (Manihot esculenta Crantz) stems quality for root production effectiveness - Yomeni, M.O.; Akoroda, M.O.; Dixon, Alfred G.O. (ISTRC-AB, 2012)
Four attributes of stem quality: number of nodes1, diameter2, and stem weight3 per 25-cm plantable stake (PS), and the stake position4 were investigated in field trials at Blocks 4, 18 and 24 of the International Institute of Tropical Agriculture (IITA) Onne, Ajibode, Ibadan, Federal College of Agriculture, Akure and Dogodawa, Zaria, Nigeria to evaluate the relationship between good quality cassava planting material and the stem and root yields and to assess the best stake position that gives the best stem and root yields. Forty three cassava mosaic disease resistant varieties were planted during the 2005 and 2008 planting seasons in a randomized complete block design with four replicates while two varieties out of the 43 in trial (TME 7 and TMS 30572) were evaluated in a uniformity trial. The studies found that there is a gradient of number of nodes per stake, weight and diameter in cassava stem from the base to the shoot tip. All cuttings of 25-cm long do not have the same number of nodes (varied from 5-16 nodes), diameter (1.8-3.1 cm) and weight (48-110 g). There was no significant difference (p>0.05) in yield among stakes from the basal, basal-middle, top-middle and top of the stem. The effect of the quality of stakes planted was shown on the percentage missing stands and was 18.2% in research farms, 32.7% (trained personnel farms) and 42.0% (traditional farms). Selection of quality stakes did not have any effect on the yields, but very necessary for improving root yield of cassava.